2019
DOI: 10.1038/s41380-019-0539-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal inflammation has a profound effect on cortical interneuron development in a stage and subtype-specific manner

Abstract: Severe infections during pregnancy are one of the major risk factors for cognitive impairment in the offspring. It has been suggested that maternal inflammation leads to dysfunction of cortical GABAergic interneurons that in turn underlies cognitive impairment of the affected offspring. However, the evidence comes largely from studies of adult or mature brains and how the impairment of inhibitory circuits arises upon maternal inflammation is unknown. Here we show that maternal inflammation affects multiple ste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 88 publications
4
28
0
1
Order By: Relevance
“…In this same animal model, and similar to data reported in human cases, a specific alteration in interneuron number was identified in the neocortex (42)-a finding supported by a number of other early-life inflammatory exposure models (142,143) and preterm birth models (4). It is likely that the migration and differentiation of these cell populations is affected, though many studies show that injury reduces or repairs in adult mice, following early-life inflammation (42,143). The important advantage of rodent models is the potential for behavioral testing, where aspects of human clinical disease can be recapitulated.…”
Section: Moderate/mild Injurysupporting
confidence: 84%
“…In this same animal model, and similar to data reported in human cases, a specific alteration in interneuron number was identified in the neocortex (42)-a finding supported by a number of other early-life inflammatory exposure models (142,143) and preterm birth models (4). It is likely that the migration and differentiation of these cell populations is affected, though many studies show that injury reduces or repairs in adult mice, following early-life inflammation (42,143). The important advantage of rodent models is the potential for behavioral testing, where aspects of human clinical disease can be recapitulated.…”
Section: Moderate/mild Injurysupporting
confidence: 84%
“…Consistent with previous studies that showed susceptibility of interneurons to perinatal insults in animal models and post-mortem human tissue, we observed differences in interneuron density following induction of EoP in both our models [ 19 , 20 , 21 , 23 , 24 , 25 , 62 ]. However, the previous published studies generally use single-hit (fetal/postnatal inflammation or hypoxia) models, failing to reflect the multifactorial etiology of EoP [ 19 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…The timing of the effect on viral infection at the beginning of the second trimester on the development of infant behavior is consistent with investigations in human fetal brain. Inhibitory interneurons are being formed in the hippocampus in this gestational window, when they are most vulnerable to maternal inflammation (Vasistha et al, 2019). Fetal development of inhibitory interneuron function, as measured by cerebral evoked potential inhibition in newborns, is associated with the development of infant attention and other self-regulatory behavior as measured with the IBQ-R Regulation dimension (Freedman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%